Analisis Tokoh Utama Dalam Naskah Randai Santan Batapi Sanggar Bungo Satangkai - Afdhal Afdhal; Wimbrayardi Wimbrayardi (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to reveal and describe the system and way of action and reaction of the main characters in the Randai Santan Batapi Sanggar Bungo Satangkai Manuscript. The type of research in this study is qualitative research with a descriptive analysis approach that aims to describe how the characters and actions of the characters in Randai Santan Batapi. The motorcycle taxi of this research is the Randai Santan Batapi Group of the Bungo Satangkai Studio. Supporting instruments are in the form of documentation results from recording tools, field data in the form of observation results, and interviews, and photo cameras. The results of the study describe that in the story of Randai Santan Batapi there is XIV Legaran story. From the journey of the Santan Batapi story, there are 6 stages starting from Exposition, Generating Circumstance, Rising Action, Climax, Denounment, and Cate Strophe. From the stages of the plot, we can find the characters in the story of Santan Batapi, Santan Batapi who has the character of a beautiful girl who has a sweet mouth and is full of sadness, Anggun Nan Tungga with a dashing and authoritative character, and Nan Domi Sutan with a wise and intelligent girl character. The characters from Randai Santan Batapi are able to perform actions and reactions in accordance with theater science in acting, even though the characters have never studied theater science in acting.